A Note on the Determinateness of the Utility Function - Allen, R. G. D. (Review of Economic Studies, 1935)
A Note on the Determinateness of the Utility Function Get access R. G. D. Allen R. G. D. Allen Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 2, February 1935, Pages 155–158, https://doi.org/10.2307/2967563 Published: 01 February 1935